Research on closed-loop quality continuous improvement system of “internet of things perception technology” - Hu Zhijie; Ma Lihua; Han Yong (SHS Web of Conferences, 2022)
“Internet of Things Perception Technology” is a professional core course in the Internet of Things engineering department. It has many knowledge points, complex content. Therefore, Teaching is difficult. This paper studies the closed-loop quality continuous improvement system of “Internet of Things Perception Technology”, including course objectives, course content, student analysis, teaching methods, scores evaluation, evaluation analysis, improvement measures and revised course goals. This closed-loop quality continuous improvement system not only improves the comprehensive ability of students, but also has strong promotion value.